THE GENERALIZATED STRATIGRAPHIC SCHEME OF THE JURASSIC OF WESTERN UKRAINE - Zhabina, N.M.; Shlapinsky, V.Ye.; Prykhodko, M.G.; Anikeyeva, O.V.; Machalsky, D.V. (Institute of Geological Sciences, NAS of Ukraine, 2017)
In Western Ukraine the Jurassic deposits are known in the Carpathians, Transcarpathian Deep, Carpathian Foredeep and Western part of the East European platform. The Generalized stratigraphic scheme of the Lower, Middle and Upper Jurassic of these regions is represented. The current stratigraphic scheme is supplemented and detalized according to modern data, analisys and re-interpretation of many-years investigations these deposits by different specialists. The characteristics of stratigraphic units: distribution, lithological and paleontological composition, position in section, thicknesses and criteria for dating are given. The most complete and precise sequence of the Jurassic stages is determined on the territory of Carpathian Foredeep and adjacent part of the platform. In other regions these deposits are present fragmentarily. The stratigraphic units are mainly dated by the complexes of macro- and microfossils. In Precarpathians predominantly there are palynocomplexes for dating the Lower Jurassic deposits, mollusks, foraminifers and palynocomplexes for Middle Jurassic, and foraminifers, mollusks and tintinnids for Upper Jurassic. In Carpathians there are ammonites and belemnites for dating the Lower and Middle Jurassic deposits, and ammonites, tintinnids, dinocysts for Upper Jurassic. Correlation of the Jurassic stratigraphic units of the Western Ukraine is done.